PEMULIHAN KESEHATAN TANAH SAWAH MELALUI APLIKASI PUPUK HAYATI PENAMBAT N DAN KOMPOS JERAMI PADI - Danapriatna, Nana; Simarmata, Tualar; Nursinah, Is Zunaini (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2012)
Increased intensity of use of inorganic fertilizers affect the soil health declinecharacterized by the decline of soil organic carbon. Attempts to paddy soil healthremediation can be conducted by using straw compost and biofertilizer which adaptive onpaddy soil ecosystems. This research aimed to study of restore of soil health and fertilitythrough the use of biological fertilizers, rice straw compost and fertilizer urea in lowlandrice. The research was conducted use factorial randomized block design consisting of twofactors, ie the combination of nitrogen fixation biofertilizer and straw compost (factor A)and nitrogen fertilizer (factor B). The results showed that the application of biofertilizer400 g ha-1 and 2 ha-1 tons of rice straw compost can restore soil health as indicated byan increase in soil organic C from 1.25% to over 2% and the increased population andactivity of bacteria.